Implikasi AI bagi Gen Z di Era Pendidikan Digital: Tantangan Pengembangan Etika Islam - Pramudita, Nafil Siraj (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This study aims to determine the Implications of AI in Education for Generation Z and the Development of Islamic ethics as a basis for utilizing the increasingly developing era, as well as the existence of various technologies that can change a person’s lifestyle or ethics. This study uses a library research method. The technique in collecting data is related to literature in the form of books, articles published online. The data used from various collections of documents which were then analyzed using content analysis techniques. The result found can be explained that the implementation of the use of AI in learning results in encouragement for students to facilitate their understanding of the learning delivered by their teachers. The application of Islamic ethics in the daily lives of Gen Z by prioritizing the teachings of the Prophet Muhammad and adapting to the times. The impact of the use of AI on Islamic ethics in reality is a value that can be said to be declining due to the increasingly developing era and digital access that can be easily used, so this is an opportunity for students in the next generation to not recognize how good and correct morals are. So it is concluded that the use of AI in learning is a fairly big problem for the next generation.